Geochemical Studies on the Role of Diadochy in the Cations Distribution in Minerals of Amphibole Group in Earth’s Crust - Rai, H.C.; Sharma, Meera; Sharma, Annapurna; Kumari, Sarita; Kumari, Reeta; Kumari, Anita (Asian Journal of Chemistry, 2010)
A series of 17 minerals belonging to amphibole group were analyzed in order to probe into the role of diadochy in their formation. All the three subgroups of amphibole are represented in these samples. Samples of each mineral have been collected from three different regions so in all 51 samples have been analyzed. All the factors controlling diadochic distribution namely ionic size, ionic charge and charge/radius ratio have been considered. Goldschmidt rules have been found to follow. Out of three parameters namely size, charge and valency, the first one seems to play pivotal role in diadochic substitutions. Stereochemical factors have also been found to influence the phenomenon significantly. The paper will enhance the understanding of formation of this important class of mineral, which have received scanty attention due to complicated crystal structures and will be useful in making new alloys.